COMMUNITY SERVICE EDUCATION PREVENTION FOR PREGNANT WOMEN ABOUT THE HIGH RISK OF PREGNANCY AT SANTY CLINIC - Rohmatun Nazilah; Barira; Nelly Rahayu (Jurnal Masyarakat Indonesia (Jumas), 2024)
Pregnancy is a very important period but it also has the potential for significant health risks. Nationally, the prevention of pregnancy complications is a top priority to reduce the Maternal Mortality Rate (AKI) through preventive efforts. At the Santy Clinic, the main challenge faced is the need to increase the health literacy of pregnant women so that they are able to recognize the symptoms of medical irregularities early. This community service activity aims to provide prevention education for pregnant women about the high risk of pregnancy at the Santy Clinic. The program will be carried out on January 16, 2025 through counseling methods, stimulation demonstrations to prevent pregnant women and high risk of pregnancy. The results of the evaluation showed an increase in maternal knowledge in Increasing the knowledge and understanding of pregnant women at Santy Clinic regarding various kinds of high risks during pregnancy, Equipping pregnant women with practical skills to carry out early detection of pregnancy danger signs, Providing a sense of calm to pregnant women and their families in facing the pregnancy transition period through correct medical understanding.